2020
DOI: 10.1101/2020.02.15.949685
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TheStreptomycesvolatile 3-octanone alters auxin/cytokinin and growth inArabidopsis thalianavia the gene familyKISS ME DEADLY

Abstract: Plants enhance their growth in the presence of particular soil bacteria due to volatile compounds affecting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Intriguingly, some VOCs produced by plant-associated bacteria, including Streptomyces , also have similar functions [ 159 ]. For example, 3-octanone produced by S. coelicolor , promotes the growth of Arabidopsis thaliana by altering auxin/cytokinin homeostasis [ 160 ]. Other VOCs produced by Streptomyces albulus inhibit the growth of the fungal pathogens Sclerotinia sclerotiorum (Family: Sclerotiniaceae) and Fusarium oxysporum (Family: Nectriaceae), which are responsible for cucumber Fusarium wilt and sclerotinia stem rot of oilseed rape, respectively [ 161 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, some VOCs produced by plant-associated bacteria, including Streptomyces , also have similar functions [ 159 ]. For example, 3-octanone produced by S. coelicolor , promotes the growth of Arabidopsis thaliana by altering auxin/cytokinin homeostasis [ 160 ]. Other VOCs produced by Streptomyces albulus inhibit the growth of the fungal pathogens Sclerotinia sclerotiorum (Family: Sclerotiniaceae) and Fusarium oxysporum (Family: Nectriaceae), which are responsible for cucumber Fusarium wilt and sclerotinia stem rot of oilseed rape, respectively [ 161 ].…”
Section: Discussionmentioning
confidence: 99%
“…MapMan visualization showed that auxin signaling genes were also highly induced after 24 h in KB001-treated plants. A recent study identified 3-octanone as a Streptomyces compound that alters auxin/cytokinin homeostasis, resulting in the promotion of root growth (Dotson et al, 2020). Auxin signaling is known to play an important role in plant growth promotion (Zamioudis et al, 2013;Spaepen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Streptomyces spp. produce 3-octanone, which has been reported to enhance root growth in Arabidopsis ( 26 ). Hexadecane promoted plant growth and induced systemic resistance in Arabidopsis plants against Pectobacterium carotovorum and Pseudomonas syringae ( 27 ).…”
Section: Introductionmentioning
confidence: 99%